Modulation Classifier - J Roopesh; Amrutha DC; Meghana Bhushan S N; Keerti Kulkarni (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
In the realm of wireless communications, automatic modulation classification (AMC) plays a crucial role in identifying the modulation type of incoming signals, enabling efficient spectrum usage in congested wireless environments and other communication systems applications. We present an AMC that takes into consideration various parameters among them the 3 major parameters are amplitude, power spectral density (PSD), and Signal to noise ratio (SNR), with the help of machine learning that is Support Vector machine in specific, within the MATLAB environment helps us in classifying the different types of signal that is QPSK, BPSK, QAM, 64QAM and PAM4.Therefore our AMC significantly contributes to the wireless communication by significantly boosting the different modulation techniques and thereby improving the spectrum efficiency.